Patient experiences of codesigned rehabilitation interventions in hospitals: a rapid review - Meg E Morris; Matthew Knight; Susan C Slade; Jeffrey Woods; Anita Hodge; Jonathan P McKercher; Janet Green; Jalal A Jazayeri; Claire Thwaites (BMJ Open, 2022)
Background Codesign strengthens partnerships between healthcare workers and patients. It also facilitates collaborations supporting the development, design and delivery of healthcare services. Prior rehabilitation reviews have focused mainly on the clinical and organisational outcomes of codesign with less focus on the lived experience of rehabilitation patients.Objective To explore patient experiences of codesigned hospital rehabilitation interventions.Design Rapid review and evidence synthesis of the literature.Data sources CINAHL, MEDLINE, Embase and Cochrane were searched from 1 January 2000 to 25 April 2022.Study selection Studies reporting patient experiences of codesigned rehabilitation interventions in hospitals.Results 4156 studies were screened, and 38 full-text studies were assessed for eligibility. Seven studies were included in the final rapid review. Five out of the seven studies involved neurological rehabilitation. All eligible studies used qualitative research methods. The main barriers to codesign were related to staffing and dedicated time allocated to face-to-face patient-therapist interactions. High-quality relationships between patients and their therapists were a facilitator of codesign. Thematic synthesis revealed that codesigned rehabilitation interventions can enable a meaningful experience for patients and facilitate tailoring of treatments to align with individual needs. Personalised rehabilitation increases patient involvement in rehabilitation planning, delivery and decision-making. It also promotes positive feelings of empowerment and hope.Conclusion This rapid review supports the implementation of codesigned rehabilitation interventions to improve patient experiences in hospitals.PROSPERO registration number CRD42021264547.